KARAKTERISTIK EDIBLE FILM BERBAHAN WHEY DAN KASEIN YANG MENGGUNAKAN JENIS PLASTICIZER BERBEDA (Characteristics of Edible Film Made from Whey Dangke and Casein that uses different types of Plasticizer) - F. Maruddin; A. Ako; Hajrawati hajrawati; M. Taufik (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
The combination of materials from dangke whey and casein can form an edible flm. The addition of a plasticizer such as glycerol, sorbitol and polyethylene glycol (PEG), in the manufacture of the edible flm can improve the characteristics of the edible flm becoming elastic, fexible and not easily fragile. The purpose of this research was to study the effect of plasticizer glycerol, sorbitol and polyethylene glycol (PEG) to the edible flm characteristics such as thickness, yield, and color (* L, * a and * b). This study was run according to completely randomized design with plasticizer types as the treatment consisted of glycerol, sorbitol, and polyethylene glycol (PEG) with a concentration of 35%. Each treatment was repeated 5 times. The results obtained indicated that the type of plasticizer did not affect the thickness of the edible flm. The yield of edible flm was 26.45 ± 0.34%, 24.53 ± 0.29%, and 22.56 ± 0.30% for glycerol, PEG, and sorbitol, respectively. The color value (*L) of edible flm was 88.40 ± 0.33 for sorbitol, 87.28 ± 0.25 for PEG, and 88.40 ± 0.33 for glycerol. The color value (*a) was 5.97 ± 0.10, 3.86 ± 0.13, and 0.09 ± 0.02, for glycerol, PEG, and sorbitol, respectively. While the color value (*b) of edible flm was 4.36 ± 0.10 for PEG, 1.32 ± 0.36 for sorbitol, and 1.10 ± 0.13 for glycerol. It was concluded that the use of sorbitol would increase brightness (*L) and the yield of edible flm. The use of glycerol has an efect on the reddish color of the edible flm (*a), while the PEG increase the yellowish color of the edible flm (*b).